Students' Perceptions about the Impact of AI Chatbots on their Vocabulary and Grammar in EFL Writing - Waziana, Winia; Andewi, Widi; Hastomo, Tommy; Hasbi, Muhamad (UIN Salatiga, 2024)
The rapid integration of AI technologies in education necessitates understanding their potential effects on language acquisition and proficiency, particularly in writing—a critical skill for EFL learners. This study aimed to investigate the types of Artificial Intelligence (AI) chatbots and scrutinize the students' perceptions about the impact of AI chatbots on their vocabulary and grammar in EFL writing. Using a mixed method, this study involved 100 undergraduate English as a Foreign Language (EFL) students from five universities in Indonesia, highlighting the various AI chatbots they employed in their digital activities. Data collection consisted of questionnaires, interviews, and observation sheets which were analyzed using quantitative descriptive statistics and qualitative thematic analysis. ChatGPT, Gemini, Perplexity, Bing Chat, Ernie, Character AI, Discord Bot, Wren, and Ginger emerged as the most widely used chatbots among the students, with reasons such as helpfulness, work simplification, skill and knowledge transfer, and ease of use serving as the primary motivations for their use. The findings revealed that a significant majority of students experienced substantial improvements in their vocabulary range, syntactic variety, and writing quality when using these AI chatbots. They also unanimously reported AI chatbots had a major positive impact on their language proficiency, particularly in the areas of vocabulary and grammar used in writing. The results of this research suggest that incorporating AI chatbots can be advantageous for improving the writing skills of EFL students. The study also addressed its shortcomings and offered recommendations for future research.